The relationship between corporate entrepreneurship and its competitiveness in China: The moderating effect of employee stock ownership plan - Yushan Cao; Mengshu Wan (Heliyon)
Using data from Chinese publicly listed companies spanning from 2010 to 2022, this study examines the relationship between corporate entrepreneurship, employee stock ownership plans (ESOPs), and corporate competitiveness. The findings show that the influence of corporate entrepreneurship on enterprise competitiveness is significantly “U-shaped”. As the degree of corporate entrepreneurship increases, it initially demonstrates a significant negative impact on enterprise competitiveness, followed by a significant positive impact. Mechanism testing reveals that the implementation of ESOPs can expedite the enhancement of corporate competitiveness. Further analysis suggests that compared to arbitrage entrepreneurship, innovative entrepreneurship can contribute to sustained enhancements in enterprise competitiveness. At the same level of corporate entrepreneurship, the increase in competitive capabilities of large companies surpasses that of Small and Medium-sized (S&M) companies. This paper provides empirical evidence and theoretical guidance for studying the economic implications of different types of corporate entrepreneurship.